(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The article talks about the peoples of Central Asia in the Middle Ages against the aggressive actions of the troops of Genghis Khan/ o the tactics used by the two sides, tactical techniques, form, methods of combat by the Khorezmshah and Mongols.